2019
DOI: 10.1016/j.jaci.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

An update on immunologic mechanisms in the respiratory mucosa in response to air pollutants

Abstract: Every day, we breathe in more than 10,000 L of air that contains a variety of air pollutants that can pose negative consequences to lung health. The respiratory mucosa formed by the airway epithelium is the first point of contact for air pollution in the lung, functioning as a mechanical and immunologic barrier. Under normal circumstances, airway epithelial cells connected by tight junctions secrete mucus, airway surface lining fluid, host defense peptides, and antioxidants and express innate immune pattern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 112 publications
(183 reference statements)
0
66
0
Order By: Relevance
“…To complement the mechanical barrier of the lung, the airway epithelium is able to produce and host-defence peptides and antiviral mediators to protect from pathogens (Parker and Prince, 2011;Huff et al, 2019). Tobacco smoke has been reported to compromise the ability of airway epithelial cells to effectively control both bacterial and viral insults (Hudy et al, 2010;Eddleston et al, 2011;Rider et al, 2011;Amatngalim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To complement the mechanical barrier of the lung, the airway epithelium is able to produce and host-defence peptides and antiviral mediators to protect from pathogens (Parker and Prince, 2011;Huff et al, 2019). Tobacco smoke has been reported to compromise the ability of airway epithelial cells to effectively control both bacterial and viral insults (Hudy et al, 2010;Eddleston et al, 2011;Rider et al, 2011;Amatngalim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Peru have explored the effect of air pollution as a determinant of asthma [27]. The most important effects of air pollution manifest in the upper respiratory tract where it alters immune response [8], contributing as a susceptibility factor for various respiratory diseases [28]. One study showed impaired the expression of CD69, IFN-γ and TNF-α when human peripheral blood mononuclear cells are exposed to Mycobacterium tuberculosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as pollution and suspended particles are considered to play important roles in the development of TB [7]. This is explained by secretion clearance impairment by epithelial cells of the respiratory tract which is the primary defense mechanism against Mycobacterium tuberculosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Airway epithelial cells carry out a number of functions such as providing a physical barrier against microbial infiltration, maintaining the inflammatory microenvironment, and releasing immune mediators to recruit leukocytes to the site of insult. It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function(30-32). Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges(31, 32).…”
Section: Introductionmentioning
confidence: 99%